1973
DOI: 10.2134/agronj1973.00021962006500010024x
|View full text |Cite
|
Sign up to set email alerts
|

Iron Utilization by Efficient and Inefficient Sorghum Lines1

Abstract: Iron‐efficient and Fe‐inefficient sorghum [Sorghum bicolor (L.) Moench.] inbred lines and their F1 hybrid differed in response to Fe deficiency. These lines were used in growth chamber studies with a soil and with several liquid‐nutrient media to determine Fe‐use efficiency. An Fe‐deficient Colby silt loam soil (5.2 ppm DTPA extractable Fe) with 22.4 kg Fe/ha and without added Fe was used for a potted‐soil, growth study. In the remaining studies seedlings were grown in Hoagland nutrient solution to induce Fe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Recently, Uvalle (1983), reported that chlorotic plants had higher contents of nitrates, phosphorus and total iron and that indicated this was the cause of the precipitation of insoluble iron phosphate in soybean. Up to now, has been reported (Miller et al, 1960;Odurukme and Maynard, 1969;Mikesell et al, 1973;Brown and Jones, 1975) that the iron chlorosis is associated with the inbalance in the P/Fe relation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Uvalle (1983), reported that chlorotic plants had higher contents of nitrates, phosphorus and total iron and that indicated this was the cause of the precipitation of insoluble iron phosphate in soybean. Up to now, has been reported (Miller et al, 1960;Odurukme and Maynard, 1969;Mikesell et al, 1973;Brown and Jones, 1975) that the iron chlorosis is associated with the inbalance in the P/Fe relation.…”
Section: Discussionmentioning
confidence: 99%
“…Mikesell e_t al. (16) reported that when FeEDTA was added to the nutrient solution increasing the concentration of P from 0 to 5 mM significantly, increased the dry weight of Feefficient sorghum plants. Increased P and Fe levels in the nutrient solution, in most instances, had little or no effect on P content of sunflower shoots for both sources of iron.…”
Section: Sabeti and Kashiradmentioning
confidence: 99%
“…Fe deficiencies in seedlings can endanger survival by restricting root and shoot growth and by reducing the plant's ability to recover from water deficits (1,7,10, 15 for a further 4 days in the light on vermiculite irrigated with 0.1 strength Hoagland solution without micronutrients. The cotyledons were removed from 6-day-old plants, and batches of 10 plants were transferred on day 7 to trays containing 8 liters of aerated, full strength Hoagland solution.…”
Section: Introductionmentioning
confidence: 99%
“…Fe deficiencies in seedlings can endanger survival by restricting root and shoot growth and by reducing the plant's ability to recover from water deficits (1,7,10,15). It is clearly important that the roots of seedlings develop rapidly into a system capable of supplying additional Fe from the soil; paradoxically, Fe deficiencies of seedlings could restrict the development of the roots.…”
mentioning
confidence: 99%